2006
DOI: 10.1016/j.jadohealth.2006.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cigarette Smoking and Media Literacy about Smoking among Adolescents

Abstract: Purpose-To determine whether media literacy concerning tobacco use is independently associated with two clinically relevant outcome measures in adolescents: current smoking and susceptibility to smoking.Methods-We asked high school students aged 14-18 years to complete a survey that included a validated 18-item smoking media literacy (SML) scale, items assessing current smoking and susceptibility to future smoking, and covariates shown to be related to smoking. We used logistic regression to assess independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
2
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 28 publications
6
79
2
6
Order By: Relevance
“…The authors still found a substantial connection between exposure to risk-glorifying media content and risk taking (g ϭ .39), which is comparable in magnitude to the mean overall effect size of the present metaanalysis (g ϭ .43). Other researchers such as Distefan, Pierce, and Gilpin (2004); Choi et al (2002);and Primack, Gold, Land, and Fine (2006) also reported adjusted effects, which ranged from between g ϭ .29 and g ϭ .31 and are thus in the same effect size range as the overall, unadjusted effect size found in our metaanalysis. In addition, the present research contains many experiments (N ϭ 25; accounting for 23.81% of all effect sizes) in which a priori differences were naturally controlled by randomization.…”
Section: Control For Potential Confounderssupporting
confidence: 82%
“…The authors still found a substantial connection between exposure to risk-glorifying media content and risk taking (g ϭ .39), which is comparable in magnitude to the mean overall effect size of the present metaanalysis (g ϭ .43). Other researchers such as Distefan, Pierce, and Gilpin (2004); Choi et al (2002);and Primack, Gold, Land, and Fine (2006) also reported adjusted effects, which ranged from between g ϭ .29 and g ϭ .31 and are thus in the same effect size range as the overall, unadjusted effect size found in our metaanalysis. In addition, the present research contains many experiments (N ϭ 25; accounting for 23.81% of all effect sizes) in which a priori differences were naturally controlled by randomization.…”
Section: Control For Potential Confounderssupporting
confidence: 82%
“…[42][43][44] The original scale has 18 items divided into three domains: authors and audiences (AA), messages and meanings (MM), and representation and reality (RR). As a result of cognitive interviews conducted for transcultural adaptation, five items were deemed not relevant; therefore, the final version of the scale consisted of 13 of the 18 items.…”
Section: Smoking Media Literacymentioning
confidence: 99%
“…Prior studies have shown an association between the level of smoking media literacy and smoking status among adolescents in the USA and in Jujuy, Argentina, as well as in US college students. [42][43][44] In a previous article, we analyzed access to tobacco company websites among medical students from UBA. 45 The objective of the present paper is to describe the attitudes and knowledge of these medical students and recent graduates towards smoking and smoking behavior, including their level of smoking media literacy, based on their smoking status.…”
Section: Introductionmentioning
confidence: 99%
“…After exposure to each clip, participants completed several measures (measures were completed after each clip exposure individually; see below). Finally, participants were debriefed; given a 45-min interactive media literacy intervention on cigarette advertising and movie smoking to help them understand, analyze, and criticize those media messages, with the goal of buffering any potentially harmful effects of clip exposure (see Brown, 2006;Primack, Gold, Land, & Fine, 2006); and compensated with $25.…”
Section: Introductionmentioning
confidence: 99%